Gastrointestinal blood loss in triathletes: it's etiology and relationship to sports anaemia - Rudzki, S. J.; Hazard, H.; Collinson, D. (1995)
Twenty male triathletes (R 18-39 mean = 27.5 yrs) provided blood and faecal samples during intense training, pre-race taper and post-competition. All answered a closed-end questionnaire on intake of aspirin, NSAIDS, Vitamin C, iron and red meat. History of GIT blood loss and training distances were also obtained. Blood samples were taken on three occasions and analysed for Haemoglobin(Hb) and Serum Ferritin concentrations. Faecal specimens were collected on five occasions and assessed for blood loss using Haemoccult II and Monohaem (a monoclonal antibody test specific for human haemoglobin). Mean Hb and 95% confidence intervals at the three stages were 14.53gm/l (13.95-15.10), 14.9gm/l (14.46-15.34), 14.57gm/l (14.18-14.97) respectively. There was a small, but statistically significant, increase in Hb during the pre-race taper period (paired t = 2.65, p < 0.05), and a non-significant drop in Hb post-event (paired t = 1.89, p = 0.075). Mean ferritin, MCV and haematocrit values did not significantly change. Eighty percent of the group exhibited faecal blood loss on one or more of the tests used. There were significant increases in both Haemoccult (chi 2 = 5.44, p < 0.04) and Monohaem (chi 2 = 7.36 p < 0.02). Regression analysis demonstrated a significant relationship between training Hb and total training intensity (R = -0.61, F1,l5 = 8.98, p < 0.009) and training run intensity (R = -0.55, F1,l5 = 6.17, p < 0.026), as estimated using Coopers aerobic points system. These results confirm that GIT blood loss is common in endurance athletes, and appears to be related to exercise intensity. The possible mechanisms of blood loss are discussed. Aust J Sci Med Sport 1995 Mar;27(1):3-8